Addition of Ceramic Barriers to Aluminum–Air Batteries to Suppress By-product Formation on Electrodes. Issue 3 (1st January 2015) - Mori, Ryohei
Abstract : We fabricated a rechargeable aluminum–air battery by placing ceramic materials such as aluminum oxide or aluminum tungsten oxide between the aqueous electrolyte, aluminum anode, and air cathode. When NaOH or KOH was used as the electrolyte, Na- or K-containing ion species might have participated in the electrochemical reaction. The cell impedance increased as the charge–discharge reaction proceeded. This increase may be due to by-product accumulation on the cell components prepared with aluminum oxide. To investigate the possibility of preventing evaporation of the liquid electrolyte in the battery, glycerin was added to the NaCl electrolyte. Because of the high boiling temperature of glycerin, the discharge reaction could continue for 5 days.